(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate the prevalence of depression, anxiety, and stress among high school students in Hanoi and identify associated factors. Methods: A cross-sectional study was conducted with 501 high school students in Hanoi from August to December 2023. Data were collected via an online survey, including demographic information and the DASS-21 scale. Data were analyzed using SPSS 27.0 with descriptive statistics, ANOVA, t-test, Chi-square test, and regression analysis. Results: The prevalence of depression, anxiety, and stress was 78.8%, 86.2%, and 76.6%, respectively. Severe and extremely severe levels were common, especially among female students. Gender was significantly associated with all depression, anxiety, and stress (p < 0.05), while school grade and type of school showed no significant differences. Conclusion: Mental health problems are highly prevalent among high school students in Hanoi, particularly in females. Early psychological interventions in schools are essential to support students and promote mental well-being.